Evaluatıon of effects of bupıvacaıne and ısoflurane on pancreas damage after renal ıschemıa-reperfusıon ınjury: An experımental study - Zeynel Abidin Erbesler; Tufan Ulcay (Ukrainian Journal of Nephrology and Dialysis, 2021)
Recent studies have shown that renal ischemia-reperfusion injury can have detrimental effects on distant organs such as the brain, liver and lungs. In this study, we aimed to investigate the effects of renal ischemia-reperfusion injury on pancreatic functions.Materials and Methods. Twenty four male adult Wistar rats were divided into four groups. Sham and control group animals were not given any medications. Animals in groups 3 and 4 were treated with epidural bupivacaine and isoflurane inhalation. Animals in all groups except for the sham group were subjected to bilateral renal ischemia for 45 minutes and subsequent reperfusion. Blood samples were collected before ischemia, immediately after reperfusion and 2h after reperfusion. Serum blood urea nitrogen, creatinine, amylase and lipase levels were measured, and pancreatic sections were histopathologically examined for the presence and severity of congestion, degenerative cellular changes, cytoplasmic vacuolization and leukocytic infiltration. Levels of malondialdehyde, endogenous antioxidant enzyme catalase and reduced glutathione were measured in pancreatic tissue sections by using colorimetric kits.Results. Serum blood urea nitrogen and creatinine levels increased in rats subjected to renal ischemia-reperfusion. There was no difference between the groups in terms of pancreatic tissue malondialdehyde, catalase and glutathione levels.Conclusion. In conclusion, bilateral renal ischemia for 45 minutes led to significant impairment in pancreatic function and changes in pancreas histology. These findings might be due to antioxidant deficiency and increased lipid peroxidation in pancreatic tissue.